PELATIHAN PENGEMBANGAN PLTMH BERBASIS MASYARAKAT MANDIRI - Djuarensi Patabang; Thomas Pagasis (JURNAL PENGABDIAN PAPUA, 2017)
The community service was conducted at the Laboratory of the Faculty of Engineering, Cenderawasih University. The topics is The Development Training of  "MHP Community-Based Self", given the potential for development of renewable energy sources potential so desperately needs a good knowledge of how business can be done to develop the potential utilization of renewable energy, especially the MHP as electricity generator spread in Papua based society. The approach offered in this activity is to provide an overview of activities that will be implemented in the development of electrical energy (MHP) based independent community. Implementation of these activities are done through training and simulation in the field how to ultimately determine the location of micro hydro power plants, and utilization of energy available in the location to be effective and efficient in their utilization, especially for the development of home industries in the villages. It is hoped this activity will produce a group of people who can develop electrical energy independent community-based MHP and produced a training module for community service learning development of micro hydro power plant (MHP). The impact of this activity can form a community of skilled, creative, innovative and independent as well as increased utilization of new and renewable energy, especially in the field of micro hydro power plant as well as the needs of the community on electrical energy can be addressed and their efforts in the community independent produktivities.Keywords: Papua, MHP, energy, produktivities